Convective heat transfer characteristics in the laminar and transition region of molten salt in concentric tube. (5th May 2017) - Chen, Y.S.; Zhu, H.H.; Tian, J.; Fu, Y.; Tang, Z.F.; Wang, N.X.
Highlights: Experiment of flow heat transfer for molten salt in concentric tube is carried out. Effect of free convection on heat transfer enhancement for laminar flow is studied. Free convection can accelerate transition from laminar flow to transition flow. Nusselt number of molten salt for laminar flow rises with increasing temperature. Heat transfer correlations for laminar and transition convection are proposed. Abstract: Convective heat transfer performances of molten salt for laminar and transition flow in concentric tube are experimentally investigated using molten salt as the hot fluid flowing through the inner concentric tube within the range of Reynolds number 300–10, 000 and Prandtl number 11–27. Heat transfer coefficients of tube side molten salt are calculated using Wilson plots and the heat transfer characteristics are studied by comparing with the traditional correlations. The results show that the laminar flow heat transfer coefficients of molten salt are higher than that of pure forced flow due to natural convection. In the transition region, the transition point to transition flow is expedited to critical Reynolds number down to 1800–2000 due to the effect of natural convection, which might increase the mean value of Nusselt number in low-Reynolds-number transition regime up to 1.3 times than that value predicted by Modified Petukhov correlation. Finally, based on the model of Churchill and Usagi, an overall correlated equation for all Re and Pr is proposed to predict the heat transfer characteristics for laminar and transition regimes. The correlated equation shows good agreement with the experiment data and higher accuracy than prior expressions for the restricted ranges of Re and Pr .